Proteins Functionalization : a Strategy that Boost the Performance of these Macromolecules for Innovative Pharmaceutical and Food Developments (2018)
ABSTRACT: Proteins are macromolecules exhibiting amphiphilic properties, good biocompatibility, biodegradability, high nutritional value, and show strong interactions with several types of active compounds via hydrogen bonding and electrostatic interactions (1). These plant or animal-derived macromolecules differ in their molecular size depending on the number of amino acids present in their structure, which in turn, are linked by peptide bonds between the carbonyl (-CO-) and amino groups (-NH) (2). This amino acid sequence has its particular three-dimensional or folded organization, which provides each protein with (i) technofunctional characteristics (i.e., gelling, emulsifying, coagulating and encapsulating capabilities, softener, adsorbents, etc); (ii) biological (i.e., nutritional value, transport, and other enzymatic functions); and (iii) bioactive (i.e., antioxidant, antimicrobial, anticoagulant or anti-inflammatory activities) characteristics, which are essential in the pharmaceutical and food fields (3). Another factor that affects the functional characteristics of proteins is their source. Thus, proteins derived from vegetable sources are larger, less flexible, and less soluble in extreme pH ranges. Further, they have a globular conformation with more hydrophobic groups hidden within the molecular structure as compared to the animal counterparts (4). However, animal-derived proteins are the most widely used due to their easy processing and water solubility. In order to match those characteristics vegetable proteins can be functionalized, making them more biodegradable and biocompatible. Moreover, they are renewable, highly available, their productions implies less natural resources, and are considered as “environmentally economical”